Unsignalized Intersection Performance Analysis (Case Study: Three-Gate Intersection 3 Project Area in RDMP RU V Balikpapan) - Sahrul Rahmadani; Maslina Maslina; Wahidin Alaudin (Interdisciplinary Social Studies, 2025)
The project area in RDMP RU V Balikpapan includes a T-junction at Gate 3, which is an un-signalized intersection frequently experiencing traffic congestion due to project worker activities and area traffic. This congestion reduces vehicle speeds and impacts road performance, especially at the un-signalized intersection on Yos Sudarso Street, Gate 3. This study aims to identify congestion causes and assess the level of service (LOS) at this T-junction within the RDMP RU V Balikpapan area. Data analysis and intersection performance calculations follow the Indonesian Road Capacity Guidelines (PKJI 2014). Observational surveys were conducted over three days: Saturday (October 26, 2024), Monday (October 28, 2024), and Tuesday (October 29, 2024), with data collected every 15 minutes over 12 hours. Results show the highest peak flow occurred on Monday, October 28, 2024, during the evening peak hour (17:30–17:45), with a traffic volume of 1,354.9 passenger car units (PCU) per hour. The capacity (c) of the un-signalized T-junction at Gate 3 is 2,637.5 PCU per hour, with a Degree of Saturation (DS) of 0.5. This corresponds to LOS category C, indicating stable but not free-flowing traffic. The intersection delay (DT) averages 5.8 seconds per vehicle. Queue probability is low, with an upper bound at 0.247% and a lower bound at 0.0065%, indicating manageable congestion levels at this intersection.